Relationship between general health, occupational stress and burnout in critical care nurses of Tabriz teaching hospitals - Farnaz Rahmani; Mojgan Behshid; Vahid Zamanzadeh; Farzad Rahmani (Iran University of Medical Sciences, 2010)
Background and Aim: Occupational stress in nursing profession can result in poor nursing care and health problems. Bornout is the other problem in nursing practice that could result in absenteeism, low energy and low nursing care efficiency. In the other hand, high stress can result in mental disorders like depression. This study was carried out to determine levels of occupational stress, burnout and general health in critical nurses of Tabriz teaching hospitals.   Materials and Method: This was a fragment of a larger cross-sectional study in which 63 nurses, working in critical care units of Tabriz teaching hospitals, were selected. Data were gathered by Occupational stress questionaire, Maslach Burnout Inventory and General Health Questionaire. Data were analyzed using Chi-square test and Pearson correlation coefficient.   Results: The findings indicated that total levels of occupational stress in majority of nurses (49.2%) was high. Regarding burnout, 44.4% of nurses had high levels of burnout in emotional exhaustation aspect and 46.0% of nurses had high levels of burnout in personal accomplishment aspect. The majority of nurses (42.4%) reported high levels of anexeity. There was a statistically significant relationship of emotional exhaustation with occupational stress (P≤0.05) and mental helth was (P≤0.05).   Conclusion: Occupational stress and burnout may have undesired influences on nursing function and mental health. Stratetegies decreasing stress and burnout can promote nursing mental health and quality of care.